Building an innovative learning organization : - Sarder, Russell (John Wiley and Sons, 2016)
Institute a culture of learning to boost organizational performance and agility What makes organizations successful? Today, most successful companies are learning organizations. "Building an Innovative Learning Organization" shows you how to join their ranks and bring your organization up to the head of the class. This book is a practical, actionable guide on how to boost performance, successfully manage change, and innovate more quickly. Learning organizations are composed of engaged, motivated employees who continually seek improvement, which leads to organizational agility and the ability to innovate ahead of the curve. When you encourage learning at every level, from the intern to the C suite, you gain a more highly skilled workforce with a greater ability to act in any situation. "Building an Innovative Learning Organization" shows you how to create this culture in your organization, with detailed explanations, practical examples, and step-by-step instructions so you can get started right away. Written by a recognized thought leader in the training industry, this informative and insightful guide is your roadmap to a more effective organization.